Teaching experience with virtual enviroments in sports psychology, before and during the Covid-19 pandemic - Barbosa-Granados, Sergio (2021)
Introduction: The objective of the study is to present a teaching experience in the field of sport psychology through virtual environments in a Colombian university during the COVID-19 pandemic. In this sense, the work of sports psychological intervention of evaluation and intervention was developed that under the reasons of forty were carried out in two stages, face-to-face and virtual. Psychological instruments were applied in order to evaluate the levels of motivation and precompetitive anxiety; finally, virtual talks and conferences were held for athletes and coaches. Among the main results, high participation and adherence to lectures and virtual intervention work was obtained in student athletes from the Technological University of Pereira.